ALCOHOL USE SCREENING IN GERIATRIC PRIMARY CARE: IMPLICATIONS FOR MENTAL HEALTH. (11th November 2018) - Albright, A; Dragan, D; Halli-Tierney, A; Carroll, D; Allen, R
Abstract: The aim of the current study is to provide comprehensive health care to older adults by assessing physical and mental health in a geriatric primary care setting, including evaluation of alcohol usage, anxiety, and depression. Under current guidelines, adults over the age of 65 should not consume more than one or two alcoholic drinks per day (Satre & Wolf, 2015). Approximately 50% of men and 33% of women who consume alcohol exceed these limits (Moose et al., 2009), which may have serious health consequences. Approximately 200 patients (mean age = 77; 74% female; 16% AA) attending an interdisciplinary geriatrics clinic in Alabama have taken part in behavioral health screenings. Problematic alcohol use was assessed using the CAGE (Ewing, 1984), which evaluates hazardous drinking behaviors. Approximately 17% of participants endorsed at least one area of concern related to alcohol use, and 6% reported clinically significant problematic drinking. Problematic drinking was significantly associated with anxiety (r = .18, p < .01) and depression (r = .18, p < .01). Adults with clinically significant CAGE scores reported higher levels of anxiety compared to adults who did not report significant problematic drinking behaviors, t(164) = -2.38, p < .05. The difference in depression scores between these groups approached significance, t(163) = -1.78, p = .08, and the average depression score for adults with clinically significant CAGE scores indicated clinically meaningful depression. Based on these findings, older adults who engage in hazardous alcohol use are at greater risk to experience clinically significant anxiety and depression.